Effectiveness of Dyella japonica and Enterobacter cloacae as biofertilizers to increase maize (Zea mays) production on andisol soil (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sembiring M, Sabrina T. 2022. Effectiveness of Dyella japonica and Enterobacter cloacae as biofertilizers to increase maize (Zea mays) production on andisol soil. Biodiversitas 23: 3338-3343. Nitrogen is a very important nutrient in plant growth because it is one of the constituents of plant cells. The availability of nitrogen nutrients in the soil is very low, and this is because nitrogen is easily leached and easy to evaporate. Application of N-fixing microbes is one way to increase the availability of nitrogen in the soil. This study aims to utilize nitrogen-fixing microbes to increase nutrient uptake, production, and efficiency of urea fertilization. The study used a factorial randomized block design (RBD) consisting of Factor I, namely biofertilizer consisting of 4 treatments, namely without the application of bacteria (N0), Dyella japonica 5g (N1), Enterobacter cloacae 5g (N2) and D. japonica 2.5g + E. cloacae 2.5g (N3). Factor II is urea fertilizer with 5 levels U0 = No urea fertilizer, U1 = 1.25 g, U2 = 2.50 g, U3 = 3.75g and U4 = 5g. Parameters observed were plant height observed in weeks I-VIII, plant nitrogen (N) uptake (mg/plant), phosphorus (P) uptake (mg/plant), potassium (K) uptake (mg/plant), and plant production (g). Sampling of plants for analysis of nutrient uptake was carried out at the end of the vegetative period, namely the 8th week, while for plant production parameters, plant samples were taken at the 12th week. The results showed that the applications of nitrogen-fixing bacteria could increase N uptake up to 89.35%, P uptake up to 79.57%, K uptake up to 48.81%, and crop production increase up to 49.76%. The applications of nitrogen-fixing microbes can streamline the use of urea fertilizer by up to 50%. In general, the best treatment is the applications of D. japonica and E. cloacae plus 2.5g urea (N3U2).
Keywords: Biofertilizer, fertilization efficiency, nitrogen nutrient, nitrogen-fixing microbes